Does Microscope Assistance in Cold Steel Tonsillectomy Reduce the Risk of Postoperative Hemorrhage? Results of a Prospective Cohort Study. (8th August 2017) - Wilhelm, Thomas; Wittlinger, Jan; Georgiew, Robert; Güldner, Christian; Hoch, Stephan; Teymoortash, Afshin; Günzel, Thomas; Stankovic, Petar
Abstract : Background . Posttonsillectomy hemorrhage (PTH) is the most feared complication. Dissection near the tonsillar capsule under microscopic view (T E m i c ) could be assumed to decrease PTH compared to traditional tonsillectomy (T E t r a d ). Methods . In this study, patients were evaluated with respect to the need for surgical control (R/N: return/no return to theater (RTT): the day of surgery[ 0 ] or thereafter[ 1 ] ). The findings at resection site and pain were measured. Results . 869 patients were included (183T E mic ; 686T E trad ). PTH requiring RTT was not seen in theT E m i c group on the day of surgery (R0) while PTH requiring RTT subsequently (R1) was seen in 1.1% of the cases. In theT E m i c group, hemorrhages without a need for surgical control were observed in 0.6% (N0) and 3.4% (N1), respectively. The corresponding rates forT E t r a d were as follows: R0, 0.3%; R1, 1.7%; N0, 0.6%; and N1, 3.6% (p > 0.05 ). Postoperative edema and local infection at resection site were proven to be predictive of PTH (p = 0.007 ). Conclusion . Microscope assistance in tonsillectomy did not statistically have an influence on the PTH even though there was a trend towards lower PTH rate in theT E m i c group. Benefit forT E m i c was observed in high-volume and long experienced surgeons.